Business Feasibility Analysis with Hydroponic System in Kendari City (Case Study of Family Garden Hydroponic Vegetable Business) - Muhammad Radhy; Yusna Yusna; Samsul Alam Fyka (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Rapid global population growth, climate change, and pressure on natural resources have driven the need for innovative and sustainable agricultural solutions. Hydroponic systems have emerged as an attractive alternative that promises to meet the world's food needs while reducing adverse environmental impacts. This study aims to determine the financial feasibility of Family Garden's hydroponic vegetable business in Poasia District, Kendari City. This research was conducted from April 2021 to July 2022 using the case study method. The research respondents were Family Garden business owners. The research variables include initial investment, operating costs, and projected income. The analytical tools used in this research are Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), Internal Rate of Return (IRR), Payback Period (PP), and Sensitivity Analysis. The results showed that the Family Garden hydroponic vegetable business is financially viable. NPV analysis at a discount factor (df) of 15% shows a value of Rp196,307,009. A net B/C of 1.93 shows that the benefits outweigh the costs, making the business feasible. The IRR of 44% shows a high rate of return on capital, more significant than the 15% discount rate. The Payback Period shows that the investment will be returned within three years, three months, and 18 days, a relatively quick payback period. Sensitivity analysis shows that the business is still viable despite a 10% decrease in seed and nutrient prices or a 15% decrease in production. This study shows that marketing crops through social media such as WhatsApp and Instagram can be an effective strategy. The business is expected to reduce production costs by selecting quality seeds, taking good care of equipment, and maintaining water quality. This research contributes to modern agricultural literature by establishing a new theory on the financial viability of hydroponic businesses in areas with limited agricultural land.